Evaluation of Teachers’ Digital Competencies in Colombia: A Qualitative Approach to the Integration of ICT in Education - Hernández-Suárez, Cesar-Augusto; Hernández-Albarracín, Juan-Diego; Rodríguez-Moreno, Javier (Journal of Ecohumanism, 2024)
This qualitative study explores Information and Communication Technology (ICT) competencies among teachers in Colombia, based on the guidelines set by the Ministry of National Education. It investigates how these skills are perceived and applied in the current educational context, highlighting their importance for the professional development of educators. Using an interpretive approach, semi-structured interviews were conducted with 53 teachers from various educational levels, intentionally selected for their participation in ICT training programs. ATLAS.ti was used to code and categorize the data, enabling a detailed analysis. The findings reveal that these skills, including basic competencies and digital content creation, are essential for effectively integrating technologies into pedagogical practices. Educators recognize the importance of information management, digital communication and collaboration, as well as innovation in teaching. However, they face challenges such as the digital divide and the need for ongoing training. The research underscores the alignment of emerging competencies with those established by the Ministry of National Education, emphasizing the importance of a comprehensive approach to teacher training. It concludes that strengthening these skills is crucial to improving educational practices and preparing students for the challenges of the 21st century.